2000
DOI: 10.1159/000045558
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Depletion in Hemodialysis Patients Treated with Polysulfone Membranes

Abstract: Background/Aims: Epidemiological, animal and human studies have indicated that selenium deficiency is a risk factor for death from malignant diseases. The mechanisms that could modify selenium status may, therefore, be of particular interest in hemodialysis patients, considering their high cancer mortality rates. We aimed at evaluating the effect of hemodialysis with polysulfone membranes on selenium status. Methods: Twenty- eight chronically dialyzed patients and 32 age-matched healthy controls were enrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
4
16
0
1
Order By: Relevance
“…Se loss was found only with polysulfone, likely due to large membrane pores [8] , and not with low-flux regenerated cellulosic membrane not allowing the passage of high molecular weight Se-binding proteins [13] .…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Se loss was found only with polysulfone, likely due to large membrane pores [8] , and not with low-flux regenerated cellulosic membrane not allowing the passage of high molecular weight Se-binding proteins [13] .…”
Section: Discussionmentioning
confidence: 92%
“…Although some studies have reported normal pre-dialysis serum Se levels [13,14] , in the majority of studies, low pre-dialysis serum Se levels have been observed in patients on standard HD, in line with our results in standard HD [3,4,9,15] . Unchanged post-dialysis serum Se levels reflect an intradialytic Se loss, which is compensated due to hemoconcentration [8] . In HDF patients, reduced post-dialysis serum Se levels provide evidence of a significantly greater Se removal into effluent solution [4] , which contributed to the more obvious decrease in post-dialysis serum Se levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poliszulfon-membrán alkalmazása során a GSHP-aktivitás és a szelénkoncentráció szignifi kánsan csökkent a hemophan-membránnal kezelt betegekhez képest. Ennek alapján úgy tűnik, hogy a poliszulfon-membrán nagyobb oxidatív stresszt okozó hatású és jobban csökkenti a szelénszintet [62,63], de ennek ellentmondó vizsgálati eredményről is beszá-moltak [64].…”
Section: öSszefoglaló Közleményunclassified